YKL-40 Correlates with Soluble CD 40 Ligand in Old Myocardial Infarction with Hypertension - Diah Kumalasari; Andi Wijaya; Anwar Santoso (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Myocardial infarction is one of the coronary artery diseases caused by plaque rupture, plaque erosion or calcified nodules, with the occurence of thrombus formation and artery occlusion. YKL-40 has a functional role in plaque fibrous formation because of its high expression during fibrosis development, vascular smooth muscle cells differentiation, elevated matrix turnover and tissue remodelling in old myocardial infarction, whereas CD40 ligand, which is stored in the cytoplasm of resting platelets, rapidly presents on the surface. After cleavage, a soluble functional CD40 ligand (sCD4OL) is generated. The aim of this study was to assess the association between YKL-40 and sCD4OL in old myocardial infarction.METHODS: This study used the cross sectional study design. Fifty six patients with old myocardial infarction were selected based on their electrocardiographical results. Among these patients, 23 subjects had hypertension and 15 subjects had hsCRP >3-l0 mg/L. YKL-40 and sCD40L were measured by ELISA method.RESULTS: There was no significant correlation between YKL-40 and sCD40L (r=0.078; p=0.569) in old myocardial infarction and in subjects with hsCRP >3-10 mg/L (r=0.524; p=0.045). However, significant positive correlations Were found in subjects with hypertension (r=0.447; p=0.029).CONCLUSIONS: Our findings showed that YKL 40 correlated significantly with sCD4OL in subjects with hypertension.KEYWORDS: myocardial infarction, ruptured plaque, coronary artery disease, YKL-40, soluble CD40 ligand